The creation of hybrid organizational form: the collaboration between biotechnology companies, research institutes and universities - Kamaluddin, Norlida; Mohd Hussein, Rohaya; Zainuddin, Anizah (2012)
The National Biotechnology Policy was launched by Malaysian government in 2005. The aim of his policy is to provide a comprehensive framework in guiding the biotechnology industries development. The government has allotted funding of RM2 billion for year 2006 to 2010 in the hope by year 2010 there will be 400 biotechnology companies being developed. Thus, the focus of this research is to study the collaboration of the biotechnology companies, research institutes and universities which will be able to fulfil the efforts of the government. Based on the strategic behaviour approach, this study hypothesizes that cooperation attributes influence the performance of the collaborative organization. Results of the multiple regressions were used to test the direct and indirect relationships among variables indicated that: 1] trust, commitment, and interdependence predict goal achievement effectiveness; 2] trust and commitment predict profitability. This study contributes to the strategic management, organizational behaviour and management literature. The findings can be a basis for managers to be aware of the elements that influenced the collaboration.